2011
DOI: 10.1186/1471-230x-11-100
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging does not improve detection of colorectal polyps when compared to conventional colonoscopy: a randomized controlled trial and meta-analysis of published studies

Abstract: BackgroundA colonoscopy may frequently miss polyps and cancers. A number of techniques have emerged to improve visualization and to reduce the rate of adenoma miss.MethodsWe conducted a randomized controlled trial (RCT) in two clinics of the Gastrointestinal Department of the Sanitas University Foundation in Bogota, Colombia. Eligible adult patients presenting for screening or diagnostic elective colonoscopy were randomlsy allocated to undergo conventional colonoscopy or narrow-band imaging (NBI) during instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…[42][43][44][45] These analyses affirm the Cochrane review, demonstrating no significant difference between HD-NBI and HD-WLE in the detection of adenomas and polyps. One of these meta-analyses additionally compared polyp miss rates between HD-NBI and HD-WLE.…”
Section: Colon Polypssupporting
confidence: 75%
“…[42][43][44][45] These analyses affirm the Cochrane review, demonstrating no significant difference between HD-NBI and HD-WLE in the detection of adenomas and polyps. One of these meta-analyses additionally compared polyp miss rates between HD-NBI and HD-WLE.…”
Section: Colon Polypssupporting
confidence: 75%
“…19 Furthermore, another systematic review including 8 randomized, controlled studies showed that NBI did not improve the detection of colorectal polyps compared with WL. 20 However, the withdrawal time is an important confounding factor that may affect the validity of these studies. Withdrawal time is a difficult endoscopic factor to regulate because we are not able to control the speed of the colonoscope over a whole colonoscopic observation, compared with video studies when only a small segment of the whole colonoscopic observation is normally recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Six meta-analyses assessed the ADR of the NBI system compared with that of white-light colonoscopy (WLI). [24][25][26][27][28] None of them found any difference in adenoma, small adenoma (<10 mm) or diminutive adenoma (<5 mm) detection rates. Another meta-analysis revealed a sensitivity comparing with Lucera and Exera II systems (Olympus Medical Systems).…”
Section: Narrow-band Imagingmentioning
confidence: 87%